2017
DOI: 10.1371/journal.pone.0177952
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the human DEK oncogene reprograms cellular metabolism and promotes glycolysis

Abstract: The DEK oncogene is overexpressed in many human malignancies including at early tumor stages. Our reported in vitro and in vivo models of squamous cell carcinoma have demonstrated that DEK contributes functionally to cellular and tumor survival and to proliferation. However, the underlying molecular mechanisms remain poorly understood. Based on recent RNA sequencing experiments, DEK expression was necessary for the transcription of several metabolic enzymes involved in anabolic pathways. This identified a poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 77 publications
(81 reference statements)
0
21
0
Order By: Relevance
“…In this study we demonstrated that the ORI-based redox indices can detect the changes directly induced by knock down of DEK gene expressions. DEK gene overexpression has been reported to reprogram metabolism in squamous cell carcinoma resulting in enhanced glycolysis and NAD + [29]. Considering that FAD/(NADH+FAD) is a surrogate indicator of intracellular NAD + /(NAD + +NADH) redox ratio [7], our data indicate that DEK knockdown changes intracellular NAD-coupled redox state.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In this study we demonstrated that the ORI-based redox indices can detect the changes directly induced by knock down of DEK gene expressions. DEK gene overexpression has been reported to reprogram metabolism in squamous cell carcinoma resulting in enhanced glycolysis and NAD + [29]. Considering that FAD/(NADH+FAD) is a surrogate indicator of intracellular NAD + /(NAD + +NADH) redox ratio [7], our data indicate that DEK knockdown changes intracellular NAD-coupled redox state.…”
Section: Discussionmentioning
confidence: 56%
“…It remains unclear which component is responsible for the observed signal change. DEK overexpression has been reported to enhance glycolysis and mitochondrial respiration spared capacity, and knockdown of DEK decreased the transcription of metabolic enzymes regulating glycolysis and NAD metabolism [29]. It would be interesting to further investigate whether FAD signal decrease in our study might be associated with the suppression of the transcription of some of the redox enzymes.…”
Section: Discussionmentioning
confidence: 77%
“…For instance, Dek knockout mice are viable and resistant to chemically induced papillomas and HPV E7 driven HNSCC. In vitro , DEK overexpression in primary keratinocytes extends life span, stimulates transforming activities of classical oncogenes, and de-regulates cellular metabolism [ 16 , 17 , 78 ]. These data are in line with, but do not prove, oncogenic activities that promote cancer development at the organismal level.…”
Section: Discussionmentioning
confidence: 99%
“…Global benefits to the tumor that are produced by a switch to aerobic glycolysis remain elusive, but studies have demonstrated a variety of likely scenarios, including evasion of the immune system, stimulation of neo-vascularization, and selection for drug-resistant cancer cell clones. Interestingly, the activation of oncogenes such as Ras [11], Akt [12], Myc [13], and Dek [14] is in and of itself sufficient for increased cellular glucose uptake and glycolysis. Given that oncogene activation is an early event in tumor development, the switch to a glycolytic metabolism and associated benefits to the tumor appear to be equally early events in the disease process.…”
Section: Aerobic Glycolysis and Lactate Metabolism: Enablers Of Tumormentioning
confidence: 99%